Rancang Bangun Receiver menggunakan Antena 1090 MHz dan Low Noise Amplifier untuk Menambah Jarak Jangkau Penerimaan Sinyal dan Data Parameter Target ADS-B berbasis RTL820T2 - Maulana Sohibi; Denny Dermawan; Lasmadi lasmadi (Aviation Electronics, Information Technology, Telecommunications, Electricals, Controls (AVITEC), 2020)
Radar technology at several airports is still using flightradar24 as a source of information, and building an ADS-B station is expensive. However, the flightradar24 has several weaknesses, among which is that if the user wants to display more information, the user is required to pay periodically or subscriptions, and there is delay due to the process of data that requires the Internet connection. With a concept of receiver ads-b based RTL-SDR R820T2, a low cost receiver ads-b with the results can receive an ads-b signal without delay and can receive data from an airplane. But there is a weakness in rtl-b receivers based RTL-SDR R820T2, because it doesn't explain and can't know how far the receiver can receive signals and target parameters data from the aircraft. Thus on this research a receiver ads-b using RTL-SDR R820T2, with a low-noise amplification and an ads-b antenna 1090 MHZ in the hopes of knowing how far the aircraft's target range is from the receiver and knowing how far the receiver's range of data signals the target parameters. By performing some step-by-step testing of the design. The designed receiver ads-b USES low noise amplification with an ads-b antenna 1090 MHZ capable of receiving data and target parameters ads-b for 284 km on adsbSCOP software range and 287.63 km mathematically.